2007
DOI: 10.1152/ajpregu.00319.2006
|View full text |Cite
|
Sign up to set email alerts
|

Expression of nestin in the podocytes of normal and diseased human kidneys

Abstract: The complex cyto-architecture of the podocyte is critical for glomerular permselectivity. The present study characterizes the expression of nestin, an intermediate filament protein, in human kidneys. In normal kidneys, nestin was detected at the periphery of glomerular capillary loops. Colabeling showed nestin was expressed in WT1-positive cells. Within the podocyte, nestin immunoreactivity was present in the cell body and primary process. This was supported by immunoelectron microscopy. Nestin also colocalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 20 publications
1
39
1
2
Order By: Relevance
“…This may explain that other mutations should be looked for. Indeed, human or animal studies have demonstrated several new mutated proteins that may play a pivotal role in the filtration barrier integrity, including laminin β2 [24], α-actinin-4 [25], CD2AP [26], Neph1 [27], Nck adaptor proteins [28], β-arrestin2 [29], ZHX proteins [30], nestin [31], and TRPC6 [32]. Over the next few years, the addition of clinical studies will be a crucial step forward and will certainly improve the ability to detect and redefine these glomerular renal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain that other mutations should be looked for. Indeed, human or animal studies have demonstrated several new mutated proteins that may play a pivotal role in the filtration barrier integrity, including laminin β2 [24], α-actinin-4 [25], CD2AP [26], Neph1 [27], Nck adaptor proteins [28], β-arrestin2 [29], ZHX proteins [30], nestin [31], and TRPC6 [32]. Over the next few years, the addition of clinical studies will be a crucial step forward and will certainly improve the ability to detect and redefine these glomerular renal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal condition, Nestin is expressed in several glomerular cell types, including mesangial cells and endothelial cells, at the early stage of development and become confined to the podocytes in mature glomeruli [13, 14]. Although Tomioka et al [9] indicated that increased Nestin expression at the tubulointerstitial areas of IgA nephropathy was associated with the deterioration of the renal function, Su et al [10] demonstrated the expression level of Nestin protein and mRNA in the kidneys of patients with IgA nephropathy and proteinuria. The authors also reported that membranous nephropathy and focal segmental glomerular sclerosis with proteinuria were significantly reduced as compared with that in normal kidney, suggesting that Nestin may play an important role in maintaining normal podocyte function.…”
Section: Discussionmentioning
confidence: 99%
“…Nestin is highly expressed in renal interstitial cells [45,46] or podocytes [47,48] after suffering from tubulointerstitial injury or Glomerular Disease. These evidences suggested that renal Nestin expressing cells may have important roles in kidney homeostasis and tissue repair.…”
Section: Discussionmentioning
confidence: 99%